Intellectual disability in international classification of Diseases-11: A developmental perspective - Satish Chandra Girimaji; Arul Jayendra V Pradeep (Indian Journal of Social Psychiatry, 2018)
Historically Intellectual Disability (ID) has been included in the International Classification of Disease and related Health Problems [ICD] and Diagnostic and Statistical manual Of Mental Disorders [DSM] from the beginning. There has been a significant change in the terminology, placement of the condition, classification, and defining features as a result of advances in unraveling the development and functionality of the brain and identifying the etiologic basis of intellectual disability. Current approaches view ID from a developmental perspective and rely on both intellectual abilities and adaptive functioning. This article looks into the salient features of “Disorders of Intellectual Development” as it is termed in ICD-11 in comparison with “Mental Retardation” as it was termed in previous ICD-10 and “Intellectual Developmental Disorder” in latest DSM-5 version, and examines the commonalities and differences.